2000
DOI: 10.1007/s003940070004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dairy food supplements on bone mineral density in teenage girls

Abstract: In this 3 year study (2 years of supplementation, 1 year follow-up), teenage girls, aged 15-18 years, were able to significantly increase their BMD at the trochanter, femoral neck and lumbar spine when supplemented with dairy product foods to a mean calcium intake of 1160 mg/d. There was also an effect seen on the BMC particularly at the trochanter and to a lesser extent at the lumbar spine. The dietary calcium intake achieved did not adversely affect body weight, fat and lean mass or blood lipid profiles. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 17 publications
6
155
0
2
Order By: Relevance
“…Eight trials with a dairy intervention found no significant effect on weight or fat change when measured (46)(47)(48)(49)(50)(51)(52). The study by Merrilees et al (47), which used a design similar to our study, found in a secondary analysis no effects of dairy on gain in body fat. In contrast, one of the dairy trials in children aged 2.5-8.8 y found that increasing dairy calcium by w600 mg/d for 6 mo resulted in significantly lower gain in body fat mass (w1.5 kg) than in a control group (53).…”
Section: Discussionmentioning
confidence: 61%
“…Eight trials with a dairy intervention found no significant effect on weight or fat change when measured (46)(47)(48)(49)(50)(51)(52). The study by Merrilees et al (47), which used a design similar to our study, found in a secondary analysis no effects of dairy on gain in body fat. In contrast, one of the dairy trials in children aged 2.5-8.8 y found that increasing dairy calcium by w600 mg/d for 6 mo resulted in significantly lower gain in body fat mass (w1.5 kg) than in a control group (53).…”
Section: Discussionmentioning
confidence: 61%
“…[21] Увеличение суммарного показателя минеральной плотности костной ткани до 1,1%, или около 9 г/см 2 за 18 мес (р = 0,017), общий показатель содержания минералов в костной ткани вырос на 2,9%, или 37 г (р = 0,035), увеличение плотности костной ткани не было однородным и отмечалось преимущественно в костях таза и нижних конечностей Регулярное употребление молока M. Merrilees и соавт. [22] Минимальное увеличение минеральной плотности костной ткани отмечено в поясничных позвонках (L II -IV ) -1,8%, максимальное -в области трохантера (4,6%) и шейки бедренной кости (4,8%; во всех случаях р < 0,05), статистически значимое увеличение минерального компонента костной ткани в области трохантера (р < 0,05) 24-месячное регулярное употребление молока, сыра или йогурта M. He и соавт. [23] Увеличение суммарного показателя минеральной плотности костной ткани в среднем на 15 г/см 2 9-месячное ежедневное употребление йогурта (125 г) у детей в возрасте 3-5 лет G. Chan и соавт.…”
Section: авторunclassified
“…There is evidence that increased intake of dairy foods and calcium may play a significant role in maintaining a healthful weight and moderating body fat (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, results across studies have been inconsistent (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and this may be attributable to major challenges in using self-reported dietary intake data. Self-reported intakes tend to be subject to underreporting bias and the underreporting of energy intake tends to be positively related to weight status.…”
mentioning
confidence: 99%